PERAN MANAJEMEN RISIKO DALAM MENINGKATKAN KINERJA PERUSAHAAN EVENT ORGANIZER - Prabowo, Eko (Bisnis Event, 2025)
Indonesia’s event and MICE (Meetings, Incentives, Conferences, and Exhibitions) industries have demonstrated rapid growth over the past decade, contributing significantly to the country’s tourism and creative economy sectors. However, this progress has been accompanied by increased exposure to external disruptions, most notably the Covid-19 pandemic. In this volatile and competitive landscape, event organizer (EO) firms are required to adopt adaptive and forward-looking risk management strategies to ensure performance sustainability. This study aims to examine the relationship between risk management and organizational performance within the Indonesian event industry, with a particular focus on the financial and operational dimensions of risk. Employing a descriptive quantitative approach, data were collected from 100 EO and MICE business operators across Indonesia. Structural equation modeling using Partial Least Squares (PLS-SEM) was applied to test the proposed model. Findings reveal that both financial risk (β = 0.297, p = 0.020) and operational risk (β = 0.370, p = 0.003) have a statistically significant and positive impact on firm performance. Together, these factors account for 69.2% of the variance in performance outcomes (R² = 0.692). The results emphasize the importance of implementing systematic and anticipatory risk management practices to enhance business resilience and competitive advantage. By identifying key risk factors that influence EO performance, this study contributes to a deeper understanding of strategic management in the event industry and offers practical implications for improving firm responsiveness amid an increasingly dynamic global environment.